Desain Outdoor Playground PAUD dengan Menggunakan Metode TRIZ - Putri Septyaningsih; widya astuti (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2020)
Outdoor playground as an important aspect to support children’s interaction ability should meet the safety standard. However, not all early childhood education (PAUD) in Indonesia has a playground that is in accordance with the standards, one of which is PAUD Harapan Bunda. It has an outdoor playground with educational teaching aids (APE) in the form of a mixture of gravel and soil. Moreover, the distance between tools have not met the standard and some of that are not suitable for the age of to the students’ age. This condition does not meet safety standards so it is to necessary to design safer outdoor playground. TRIZ (Theory of Rezhenija Izobretatelskih Zadach) is the method that produce a specific solution based on the problem contradiction. Hence, this paper aims to design an outdoor playground using the TRIZ method. The first step is user’s need identification process using a questionnaire. Five needs were identified: safe, durable, attractive, supporting sensory development and sufficient space for children. The next process is determining the design parameters. This process consists of technical characteristics recapitulation, determination of the situation model and direction of innovation as a design reference. The results of the outdoor playground design consisted of loft typed smart play as the main tool, synthetic turf surface and animals picture wall. The result of Chi Square’s design validation shows that the design is in accordance with user needs.